PENDIDIKAN KARAKTER PADA SASTRA LISAN BALI - I Made Suweta (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2018)
One of the sociocultural societies of Indonesia that can be lifted as a character educationis the oral literature that is spread in various regions in this archipelago. Oral literature is anoral text as part of folklore which is a local wealth of genius that needs to be dug and empoweredas much as possible for the benefit of character education in order to improve Indonesian humanresources that are more qualified, resilient, unyielding, tenacious, diligent, honest, hard work,eroik, religious, ethical, able to cooperate, statesman, obey the law, willing to sacrifice, serve,and other characters. There is also the formulation of the problem studied in this paper is howthe form of character education in oral literature in Bali?. The theories used in assessingcharacter education in oral literature Bali are: value theory, structuralism, and semiotics. Likewisethe methods used in this study include data discovery methods and data analysis methods. In thediscovery of the data used the method of listening on previous studies as a documentation oforal literature in Bali, while in the data analysis used descriptive qualitative analysis method,which continues with the presentation of data with a combination of techniques of inductive anddeductive techniques. Based on the description of the eighteen character education values:religious, honest, tolerant, disciplined, hard work, creative, independent, democratic, curiosity,spirit of nationalism, love of the homeland, respect for achievement, friendship / communicative,love to read, care about the environment, social care, and responsibility; in the study of charactereducation in oral literature in Bali found fifteen values of character education are: religiousvalues, honest, tolerance, discipline, hard work, creative, independent, the spirit of nationality,love the homeland, friendly / communicative, love peace, , environmental care, social care, andresponsibility.